2021
DOI: 10.1016/j.jecp.2020.105010
|View full text |Cite
|
Sign up to set email alerts
|

How do children with developmental language disorder extend novel nouns?

Abstract: Highlights • Children with DLD are impaired in extending substance names and relational nouns. • Vocabulary has an impact on novel noun extension. • Comparison is beneficial for new word extension, especially in children with DLD. • Children with DLD rely on shape when extending new nouns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
0
9
0
4
Order By: Relevance
“…This claim is further supported by Krzemien et al (2021), who found that some aspects of lexical acquisition (i.e., word generalization) were similar to TD age-matched children when they were controlled for their vocabulary, which suggests that DLD learners' language abilities are delayed rather than deviant. Mohammadi et al (2011) noted that the lower definitional skills of learners with DLD are due to their language difficulties, which prevent full meaning representations.…”
Section: International Journal Of Research Studies In Education 99mentioning
confidence: 69%
“…This claim is further supported by Krzemien et al (2021), who found that some aspects of lexical acquisition (i.e., word generalization) were similar to TD age-matched children when they were controlled for their vocabulary, which suggests that DLD learners' language abilities are delayed rather than deviant. Mohammadi et al (2011) noted that the lower definitional skills of learners with DLD are due to their language difficulties, which prevent full meaning representations.…”
Section: International Journal Of Research Studies In Education 99mentioning
confidence: 69%
“…Other studies suggest that the delayed production of formal definitions in learners with DLD, is due to differences in lexical and metalinguistic development (Marinellie & Johnson, 2002). This claim is supported by Krzemien et al (2021), who found that some aspects of lexical acquisition (i.e., word generalization) were similar to TD age-matched learners when learners were controlled for their vocabulary, which suggests that learners with DLD language abilities are delayed rather than deviant. Mohammadi et al (2011) noted that the definitional skills of Persian-speaking learners with DLD were weaker due to their language difficulties which prevent the full meaning representation.…”
Section: Definitional Skills Of Learners With and Without Language Disordersmentioning
confidence: 90%
“…Their results indicated that young children with DLD tend to be less consistent when they have to choose between shape, colour or texture in word extension. Krzemien et al (2021) extended these findings and showed that this shape bias, particularly relevant for solid and animate objects, does develop in older children with DLD. Nevertheless, these authors also highlighted difficulties in word extension for categories defined by other types of features such as texture, functional roles or spatial relations.…”
Section: Introductionmentioning
confidence: 53%
“…This appeared in the study of Aguilar et al (2018), which showed better word generalization performances when the learning context involved a high variability of exemplars. This also seems to be the case in Krzemien et al (2021), who showed that school-aged children with DLD benefited from the comparison of several exemplars of a referent (and thus more opportunities to detect regularities) to extend words for texture-or spatially-based categories. However, category-based inference and statistical learning in the context of lexical and particularly semantic aspects of word learning in children with DLD has rarely been explored until now (Obeid et al, 2016).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation